An exploratory study of the impact of the Capability Maturity Model on the organizational performance of Indian software firms - Panchapakesan, P.; Ganesh, L. S.; Rajendran, C. (The Quality Management Journal, 2008)
This study aims to determine the operating elements of various levels of the Capability Maturity Model (CMM®) and important indicators of organizational performance (IOPs) in the software industry. The various levels of CMM act as critical factors (CFs), which are the input variables necessary to implement CMM. IOPs are the output variables on which the effect of implementing CMM is measured. The current levels of presence of the CFs and IOPs and the changes in the CFs and IOPs due to CMM implementation were determined in this study using two types of scales, namely, level scale and change scale, in order to measure (or capture) and analyze the perception of respondents in this research. Many interesting and valuable insights are provided. It has been found that most of the firms find it easier to set standards than to improve further. Moreover, financial gains are not immediate, and firms must strive to continuously improve in order to gain financially from CMM implementation. The study also revealed that CMM implementation has a significant positive change on organizational performance.